Financial Leverage, Firm Size, Company Age, and Earning Persistence: Evidence From Indonesia - Sinta Setiana; Bram Hadianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Everlasting earnings are needed for the firms to continue their business, and it becomes an expectation for the stakeholders, such as creditors, shareholders, and managers. Therefore, this study intends to prove the determinants of these earnings persistence. At least three factors are available based on the literature review: financial leverage, firm size, and company age. To make the study focus, it treats financial leverage as the primary variable, and the others become the control. By utilizing the quantitative design based on statistical testing, this study attempts to answer this issue. This study uses the firms in the infrastructure, utilities, and telecommunication sectors in the Indonesian capital market as the population and samples, the probability of t-statistic in the regression model to examine the prearranged hypotheses to achieve this destiny. Once analyzing the data from 2016 to 2019 of 25 companies taken by the simple random sampling technique, this research demonstrates that financial leverage and company age negatively influence this persistence; however, company size exhibits a positive impact. Based on the primary relationship evidence, this study suggests that firms reduce debt levels to avoid future failure, technical insolvency, and bankruptcy. Therefore, they can create earnings persistence from their managed business.